Study on the Meshing Characteristic of Cylindrical Gear with Arcuate Tooth Trace based on the Processing Principle of Parallel Link Mechanism - Dengqiu Ma; Zhenhuan Ye; Yu An; Fei Li; Fangzhou Chen; Xiaoyu Liu (Jixie chuandong)
The cylindrical gear with arcuate tooth trace is regarded as the research object. Based on the processing principle of parallel link mechanism，the gear tooth surface equation is derived，and the 3D model of gear is established，and the dynamics analysis model of gear pair is further established. Through the dynamics analysis simulation，the influence of tooth line radius， tooth width，load and speed on the meshing characteristics is analyzed. The results show that, the maximum meshing force， average meshing force and RMS of meshing force all decrease first and then increase with the increase of the tooth width. The maximum meshing force，average meshing force and RMS of meshing force all decrease first and then increase with the increase of tooth line radius，it’s optimum at RT=120~240 mm，the fluctuation range of average meshing force and RMS of meshing force is small，while that of maximum meshing force is large. The meshing force increases gradually with the increase of load，but the positive/negative fluctuation amplitude decreases with the increase of load. The transmission stability is poor at low loads，and even the gear transmission appears to be out of mesh. With the increase of rotating speed，the average meshing force and maximum meshing force increase，while the minimum meshing force decreases， that is， the more severe the fluctuation of gear meshing force，the greater the impact of gear transmission.